Clinical Study Primary Myocardial Disease - Batillana Guanilo, Carlos Alberto (1971)
We studied 26 patients with cardiomyopathy in the span of 10 years ( 1960-1970 ) , and originating from different regions of the country; 24 cases were males and 2 were females. Thirteen patients corresponded to the called idiopathic cardiomyopathy , 8 were related to alcoholism , 3 were familial, a case of postpartum disease and one with endomyocardial fibrosis . The ages ranged from 13 to 65, with an average of 41.8 years. Clinically, all patients, except one , had manifestations of heart failure with varying physical findings predominance the existence of cardiomegaly , systemic venous hypertension and gallop . In only one case the symptoms were related exclusively to multiple embolism. The most common arrhythmias were extrasystolic type , having demonstrated atrial fibrillation or flutter in 5 cases. The electrocardiographic patterns were also varied , showing preferably a combination lock intraventricular low voltage ; electrocardiogram was within normal limits in only one patient , who died with cardiomegaly and heart failure. Radiology showed a predominance of cardiac enlargement left cavities in virtually all cases. Fourteen patients died, necropsy performed on all of them . Macroscopic study of the heart was abnormal in 13 cases , showing dilatation and hypertrophy , only one case of a heart was found normal appearance . However, in all cases studied histology indicated that mainly changes committed to the myocardial fibers in the form of myocytolysis , nuclear changes and unspecific changes in the interstitial tissue ; these alterations were common to many patients and not keep apparent relation to the different clinical pictures. Abnormalities or inflammatory atherosclerotic were negligible.